Maldives : Technical Assistance Report-Revising the Fiscal Responsibility Act. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
The Fiscal Responsibility Act (FRA) came into effect in 2013 to reduce rising public debt and achieve fiscal stability. Maldives has experienced rapid public debt accumulation over the past decade. The FRA establishes objectives for maintaining debt at a sustainable level and reducing the overall fiscal balance. The Act also sets minimum standards for fiscal transparency and accountability and requires the Government to prepare and publish medium-term fiscal and debt strategy reports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Senegal